Electrolytic capacitor having both high temperature durability and low temperature stability and method for manufacturing the same
By combining the electrolyte solution that meets the specific viscosity and temperature relationship with sintered foil or conventional etched foil, the problem of insufficient durability at high temperature and poor stability at low temperature is solved, and the high-temperature durability and low-temperature stability of the capacitor are achieved, thereby improving its reliability and capacity.
Patent Information
- Application Number
- CN202510105828.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing electrolytic capacitors have insufficient durability at high temperatures and poor stability at low temperatures, which affects their reliability.
By combining an electrolyte solution that satisfies the specific viscosity and temperature relationship with a sintered foil or a conventional etched foil, an electrolytic capacitor that takes into account both high-temperature durability and low-temperature stability is prepared.
The electrolytic capacitor is achieved in taking into account the durability and stability at high temperatures, improving the reliability of the capacitor, and improving the capacitance at the same size.
Smart Images

Figure CN119542034B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytic capacitors, and in particular to an electrolytic capacitor having both high-temperature durability and low-temperature stability and a manufacturing method thereof. Background Art
[0002] In recent years, there has been an increasing demand for miniaturized electrolytic capacitors in the UPS, car charger, server power supply and other markets. Among them, the improvement of the unit capacity of the positive electrode material is one of the key technologies for capacitor miniaturization. Taking aluminum electrolytic capacitors as an example, the positive electrode material is etched on the surface of high-purity aluminum foil by chemical or electrochemical methods to increase its surface area to become a corroded foil, and then Al is generated on the surface of the corroded foil by anodization. 2 O 3 , making it a positive electrode material including a current collector and a dielectric. However, there is a theoretical limit to the increase in surface area based on etching. In recent years, there have been reports on methods of increasing the specific surface area of aluminum foil by sintering metal powder on the surface of the current collector. Related prior art includes: CN 102017034 B "Electrode material for aluminum electrolytic capacitors and method for manufacturing the electrode material".
[0003] Compared with the traditional etching process, the specific surface area of aluminum foil made by sintering aluminum powder can be increased by 20~40%. However, there are great differences in the structure of etched foil and sintered foil: aluminum powder sintered foil is a sponge-like porous structure, and traditional etched foil forms a tunnel pore structure by etching and expanding the surface of the aluminum foil. Therefore, the two types of aluminum foils have different requirements for matching the physical properties of the electrolyte (such as viscosity, conductivity, flash voltage, etc.). When the electrolyte penetrates the micropores on the surface of the aluminum foil, the porous structure in the sintered foil is almost completely connected, and the penetration speed is faster; while the micropores of the traditional etched aluminum foil are tunnel pore structures, which are isolated from each other and the penetration speed is slower.
[0004] Electrolytic capacitors have a relatively wide operating temperature range (e.g. -40°C ~ +105°C). When working at different ambient temperatures, the viscosity of the electrolyte in the capacitor affects its penetration rate into the micropores in the aluminum foil, which in turn affects the self-healing properties of the capacitor. Therefore, the viscosity of the electrolyte system is crucial to improving the reliability of sintered foil capacitors.
[0005] As we all know, if the electrolyte viscosity drops significantly at high temperature, too low electrolyte viscosity will accelerate the loss of electrolyte, which will have an adverse effect on the high temperature durability of the capacitor, and thus reduce the high temperature reliability of the capacitor; if the electrolyte viscosity increases and decreases significantly at low temperature, too high electrolyte viscosity is not conducive to the flow of electrolyte, which will slow down the repair rate of the electrolyte. When there are defects in the capacitor, it may lead to untimely repair, which in turn causes fatal failure of the capacitor. Summary of the invention
[0006] In order to take into account the technical problems of high temperature durability and low temperature stability of capacitors, an electrolytic capacitor having both high temperature durability and low temperature stability and a manufacturing method thereof are proposed. The present invention combines an electrolyte that satisfies a specific viscosity and temperature relationship with a sintered foil or a conventional etched foil to obtain an electrolytic capacitor having both high temperature durability and low temperature stability; the combination of an electrolyte that meets a specific viscosity and temperature relationship with a sintered foil has a higher capacitance than the combination with a conventional etched foil.
[0007] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0008] The present invention provides an electrolytic capacitor having both high temperature durability and low temperature stability, comprising a core, wherein the core comprises a positive electrode foil, a negative electrode foil and a separator disposed therebetween, including but not limited to a winding type, a stacking type, a patch type, etc.;
[0009] and an electrolyte solution impregnated and permeated into the core;
[0010] The electrolyte satisfies the exponential relationship curve of the following formula 1: or =A×e x ······Formula 1;
[0011] Where A is a constant whose value is 1.378×10 -5 ~3.461×10 -5 Within the range; x=B÷T, B is a constant whose value is within the range of 4298~5052;
[0012] in or is the viscosity of the electrolyte, in mPa·s; T is the Kelvin temperature, which ranges from 248.15K to 363.15K; e is the base of the natural logarithm, which is approximately equal to 2.71828.
[0013] Another aspect of the present invention provides a method for manufacturing the electrolytic capacitor having both high temperature durability and low temperature stability, comprising the following steps: forming a core by stacking a positive electrode foil, a separator, and a negative electrode foil in a stacking order, impregnating the core with an electrolyte, placing the core in a housing, and sealing the core with a seal; wherein the core end has a lead foil connected to a lead end outside the seal;
[0014] The electrolyte satisfies the exponential relationship curve of the following formula 1: or =A×e x ······Formula 1;
[0015] Where A is a constant whose value is 1.378×10 -5 ~3.461×10 -5Within the range; x=B÷T, B is a constant whose value is within the range of 4298~5052;
[0016] in or is the viscosity of the electrolyte, in mPa·s; T is the Kelvin temperature, which ranges from 248.15K to 363.15K; e is the base of the natural logarithm, which is approximately equal to 2.71828.
[0017] Furthermore, the exponential relationship curve satisfied by the electrolyte is within the range of the upper limit exponential relationship curve of Formula 2 and the lower limit exponential relationship curve of Formula 3:
[0018] The upper exponential relationship curve is or =1.378×10 -5 ×e x ······Formula 2, where x=5052÷T;
[0019] The lower limit exponential relationship curve is or =3.461×10 -5 ×e x ······Formula 3, where x=4298÷T.
[0020] That is, all electrolytes within the range of the upper exponential relationship curve of Formula 2 and the lower exponential relationship curve of Formula 3, whether combined with sintered foil or conventional etched foil, can achieve the effect of taking into account both better high temperature durability and low temperature stability.
[0021] Furthermore, in the formula 1, A is a constant whose value is between 2.25×10 -5 ~3.48×10 -5 B is a constant whose value is in the range of 4380~4680. The curve fitting degree R of formula 1 is 2 >0.998.
[0022] More preferably, the exponential relationship curve satisfied by the electrolyte is or =2.2888×10 -5 ×e x ······Formula 1-1, where x=4658.9÷T, R 2 =0.99885;
[0023] Or the exponential relationship curve satisfied by the electrolyte is or =2.4938×10 -5 ×e x ······Formula 1-2, where x=4674.9÷T, R 2 =0.99838;
[0024] Or the exponential relationship curve satisfied by the electrolyte is or =3.4699×10 -5 ×e x ······Formula 1-3, where x=4385.8÷T, R 2 =0.99949.
[0025] Furthermore, the positive electrode foil is an etched foil or a sintered foil.
[0026] Furthermore, the sintered foil is sintered on the surface of the current collector by sintering metal powder to achieve surface expansion, and the median diameter of particles on the surface is less than or equal to 7 μm.
[0027] Furthermore, the electrolyte includes a solute and a solvent;
[0028] The solute is a polyacid ammonium salt and / or a polyacid amine salt;
[0029] The anions in the polyacid ammonium salt and the polyacid amine salt are each selected from a polycarboxylic acid group or a polyboric acid group;
[0030] The cation in the polyacid ammonium salt is NH 4 + ;
[0031] The cation in the polyacid amine salt is selected from primary amine salt NH 3 R + 、Secondary amine salt NH 2 R 2 + , tertiary amine salt NH 3 R + One of the following, wherein R represents an alkyl group having 1 to 15 carbon atoms.
[0032] Polyacid ammonium salts include 1,6-dodecanedioic acid ammonium, ammonium azelaic acid, ammonium sebacate, ammonium pentaborate, etc.; polyacid amine salts include diethylamine azelaic acid, trimethylamine azelaic acid, etc.
[0033] Furthermore, the electrolyte also includes additives, and the additives are selected from one or more of flash stabilizers, anti-hydration agents, and hydrogen absorbers.
[0034] Beneficial technical effects:
[0035] The present invention adopts sintered aluminum foil or conventional etched foil with increased surface expansion coefficient and electrolyte that meets the specific upper and lower limit exponential relationship curve. While ensuring the miniaturization of the capacitor size, combined with the optimal viscosity and temperature relationship of the electrolyte, an electrolytic capacitor with both good high-temperature durability and low-temperature stability can be obtained; in addition, the hole characteristics of the sintered foil are fully considered, and the combination of the electrolyte that meets the specific viscosity and temperature relationship and the sintered foil has a higher capacitance than the combination with the conventional etched foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a cross-sectional view of an aluminum electrolytic capacitor manufactured in an embodiment, and does not show the decomposed state of the positive electrode foil, the negative electrode foil, and the separator wound structure disposed therebetween, and the impregnated electrolyte;
[0037] Figure 2 The leakage current data of each capacitor during low temperature power-up process;
[0038] Figure 3 is the viscosity of the electrolyte of Example 1-3 or The relationship curve with the inverse of temperature T;
[0039] Figure 4 is the viscosity of the electrolyte of Comparative Example 1-2 or The relationship curve with the inverse of temperature T. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0042] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.
[0043] What needs to be noted about the expression of values is that: the expression “the value is within the range of…” does not include the endpoint values; the expressions “the value is…” or “the value is…” include the endpoint values.
[0044] The electrolyte used in the following aluminum electrolytic capacitors includes a solvent, a solute and an additive, wherein the additive includes a flash stabilizer, an anti-hydration agent and a hydrogen absorber.
[0045] Solvents
[0046] As the solvent, the main function of which is to dissolve the electrolyte and the additives, an organic solvent is preferably used alone, or a mixture of an organic solvent and water may be used.
[0047] The solvents in the following examples may be organic solvents alone, wherein polyols and lactones are representatives of protic solvents and aprotic solvents. Protic solvents include but are not limited to ethylene glycol, diethylene glycol, glycerol, 1,2-propylene glycol, 1,3-propylene glycol, butanol or related derivatives; aprotic solvents include but are not limited to γ-butyrolactone, cyclopentane sulfone, methyl cyclopentane sulfone, N,N-dimethylformamide or related derivatives.
[0048] It is also possible to use a mixture of organic solvent and water. The organic solvent-water mixture system can lower the freezing point of the solvent and improve the low-temperature characteristics of the electrolyte to some extent.
[0049] The ratio of protic solvent, aprotic solvent and water in the solvent system has a direct impact on the viscosity-temperature characteristics of the electrolyte.
[0050] Solute
[0051] The solutes in the following embodiments are polyacid ammonium salts and / or polyacid amine salts, which can be obtained by acid-base neutralization reaction between organic carboxylic acids (preferably polyacidic straight-chain or branched carboxylic acids), or inorganic acids and their salts (preferably boric acid complexes and their salts) and organic amines or inorganic ammonia.
[0052] The cation in the polyacid ammonium salt is NH 4 + , the anion is a polycarboxylic acid group or a polyboric acid group. The polyacid ammonium salts include 1,6-dodecanedioic acid ammonium, azelaic acid ammonium, sebacate ammonium, pentaborate, etc.;
[0053] The polyacid amine salt cation is a primary amine salt NH 3 R + 、Secondary amine salt NH 2 R 2 + , tertiary amine salt NHR 3 +One of the above, wherein R represents an alkyl group of 1 to 15 carbon atoms, and the anion is a polycarboxylic acid group or a polyboric acid group. The source of the polyacid amine salt cation is methylamine, ethylamine, dimethylamine, diethylamine, trimethylamine, triethylamine, ethyldimethylamine, diethylmethylamine, etc. The polyacid amine salt is for example diethylamine azelaic acid, trimethylamine azelaic acid, etc.
[0054] These solutes can be used alone or in combination.
[0055] additive
[0056] The additives in the following embodiments include a flash stabilizer, an anti-hydration agent, and a hydrogen absorber.
[0057] The flash stabilizer mainly functions to stabilize the flash voltage of the electrolyte. Examples include but are not limited to: water-soluble silicone, polyacrylic acid or its derivatives, polyethylene glycol or its derivatives, polyvinyl alcohol or its derivatives, polyoxyethylene glycol or its derivatives, polysiloxane, nano-silicon dioxide, etc. They can be used alone or in any combination of two or more.
[0058] The main function of the anti-hydration agent is to inhibit the hydration reaction between the positive electrode foil, the negative electrode foil and water, reduce the generation of hydrogen, and increase the life of the capacitor. Common anti-hydration agents include phosphates or phosphate esters, sugars, and aluminum silicate compounds.
[0059] Hydrogen absorbers are mainly nitro compounds, which are used to absorb hydrogen generated when the capacitor is working, reduce the internal pressure of the capacitor, and extend the life of the capacitor.
[0060] Example 1-Example 3
[0061] The electrolyte ratios of Examples 1-3 are shown in Table 1.
[0062] Comparative Example 1-2
[0063] The electrolyte ratios of Comparative Examples 1-2 are shown in Table 1.
[0064] The materials were prepared according to the mass percentage ratios in Table 1 and stirred evenly to obtain the electrolytes for each case.
[0065] Table 1 The mass percentage ratio of each material in the electrolyte of each case
[0066]
[0067] Manufacturing example
[0068] The cross-sectional structure of an aluminum electrolytic capacitor is as follows: Figure 1 As shown, the specific manufacturing method comprises the following steps:
[0069] The positive electrode foil, the separator, and the negative electrode foil are wound in a stacking order to form a core (of course, in other embodiments, the core can be formed in a stacked form, and the present invention takes a wound core as an example; the separator is a conventional electrolytic paper), and the positive electrode foil is a sintered foil or a conventional etched foil; the core is impregnated with an electrolyte, placed inside an aluminum metal shell, and then sealed with a seal; wherein the end of the core has a lead foil and is connected to the lead end outside the seal, and a high-voltage aluminum electrolytic capacitor is obtained after aging.
[0070] The capacitors made of sintered foil have specifications of 450v1000μF, 30mm diameter and 60mm height;
[0071] The sintered foil used is provided by Dongyangguang. The metal powder sintered on the surface is aluminum powder. The purity of the aluminum powder sintered on the surface is greater than 99.99%, and the median diameter of the aluminum powder is ≤6μm. After the aluminum foil is energized, the withstand voltage is 650VF and the specific capacitance is 0.78μF / cm 2 .
[0072] For comparison, the capacitor specification is 450V820μF made of etched foil with the same size (30mm diameter, 60mm height). The etched foil used is provided by Jianghai, and the withstand voltage of the aluminum foil is 650VF and the specific capacitance is 0.65μF / cm 2 .
[0073] The separator used is electrolytic paper made of fiber materials such as wood fiber and hemp fiber, and the density of the electrolytic paper is 0.55g / cm 3 ~0.85g / cm 3 , thickness is 40μm~70μm.
[0074] Test Case
[0075] 1. High temperature durability evaluation
[0076] In order to evaluate the impact of the electrolyte in each of the above cases on the high temperature durability of the capacitor, tests were conducted according to the durability standard GB / T 6346.1-20248.5: test temperature Ta = 105 ° C, working voltage Vp = 450v, and ripple currents of 2.7A and 3A @ 120Hz were applied to 450v820μF and 450v1000μF respectively. The test results are shown in Table 2.
[0077] Table 2 High temperature durability data of capacitors
[0078]
[0079] It can be seen from Table 2 that the electrolyte viscosity has a significant effect on high temperature durability when combined with sintered foil or etched foil. After 3000h high temperature durability test, the capacity change of sintered foil combined with electrolytes of Examples 1 to 3 is within -5%.
[0080] In Comparative Example 1, the electrolyte is combined with sintered foil, and its high-temperature durability is not affected. In Comparative Example 2, the electrolyte is combined with sintered foil, and after high-temperature durability test, the capacity has been greatly attenuated (-11.42%), and the loss is more than three times the initial value. In Comparative Example 2, the electrolyte is combined with etched foil, and the loss is more than three times the initial value after high-temperature durability test. Due to the low high-temperature viscosity of the electrolyte in Comparative Example 2, when combined with sintered foil or etched foil, the change in the 3000h high-temperature durability test parameters exceeds the judgment requirements, and the result is NG.
[0081] In addition, it can be seen from Table 2 that, compared with conventional etched foil, the capacity of the capacitor made by combining the sintered foil with the electrolyte of the embodiment is increased by at least 20%. Under the same size, the capacity of the capacitor is increased by at least 20%, realizing the miniaturization of high-capacity products.
[0082] 2. Low temperature stability assessment
[0083] In order to evaluate the effect of different electrolytes on the low temperature stability of capacitors, the following verification tests were carried out:
[0084] (1) Place the capacitor in a -40℃ environment and freeze it for 1000 hours;
[0085] (2) In a -40°C environment, apply a 10A@120Hz ripple current to the capacitor;
[0086] (3) Record the change in capacitor leakage current within 5 minutes after power-on.
[0087] Note: The verification test steps simulate the working conditions of capacitors after outdoor storage in cold regions, such as outdoor charging piles, electric vehicles parked outdoors, etc., which are directly fully loaded after long-term storage at low temperatures.
[0088] The leakage current during power-on can be used as a reflection of the low-temperature stability of the capacitor. The larger the leakage current, the higher the risk of the capacitor failing at low temperatures and the worse its low-temperature stability.
[0089] The test results are shown in Table 3 and Figure 2 .
[0090] Table 3 Leakage current data of capacitors during low temperature power-up
[0091]
[0092] From Table 3 and Figure 2 It can be seen that the sintered foil is combined with the electrolytes of Examples 1 to 3 and Comparative Example 2, respectively, and the etched foil is combined with the electrolyte of Example 1. After being frozen at -40°C for 1000 hours, a 10A ripple current is continued to be applied at -40°C, and the capacitor leakage current can be quickly reduced to less than 1.5mA within 2 minutes.
[0093] After the sintered foil and the etched foil were combined with the electrolyte of Comparative Example 1 and frozen at -40℃ for 1000h, a 10A ripple current was applied at -40℃. The maximum capacitor leakage current was 96mA and 49mA respectively, and after 5min of repair, it was still as high as 9mA and 4mA, far exceeding the standard of 1.5mA. This shows that the high viscosity of the electrolyte of Comparative Example 1 at low temperature leads to slow ion migration and low repair rate of defects on the surface of the positive foil, resulting in a sharp increase in the final capacitor leakage current and an increased risk of capacitor failure.
[0094] In order to explore the reasons for the above differences, the electrolytes in the above cases were tested for viscosity changes with temperature using a rotational viscometer. The test method refers to GB / T 22235-2008 "Determination of Liquid Viscosity". Specific test data are shown in Table 4 below. The reciprocal of temperature T (1 / T) is used as the horizontal axis and the viscosity is used as the horizontal axis. or As the ordinate, curve fitting is performed. The curve fitting equation is shown in Figure 3 and Figure 4 .
[0095] Figure 3 and Figure 4 The dotted solid line in the figure is the measured data in Table 4, and the dashed line is the curve fitting based on the measured data of each case. Figure 3 and Figure 4 For example, E+00 is 10 0 times, E-01 is 10 -1 times, R 2 is the fit of the curve.
[0096] Table 4 Measured data of electrolyte viscosity changing with temperature in each case
[0097]
[0098] From the data in Table 4 and Figure 3 , Figure 4 It can be seen that the curve fitting results of Example 1-Example 3 and Comparative Example 1-Comparative Example 2 are exponential relationship curves, as follows:
[0099] The curve fitting equation of Example 1 is: or =2.2888×10 -5 ×e x ······Formula 1-1, where x=4658.9÷T(R 2 =0.99885);
[0100] The curve fitting equation of Example 2 is: or =2.4938×10 -5 ×e x······Formula 1-2, where x=4674.9÷T(R 2 =0.99838);
[0101] The curve fitting equation of Example 3 is: or =3.4699×10 -5 ×e x ······Formula 1-3, where x=4385.8÷T(R 2 =0.99949);
[0102] The curve fitting equation of Comparative Example 1 is: or =1.002×10 -5 ×e x ······Formula 2-1, where x=5914÷T(R 2 =0.9997);
[0103] The curve fitting equation of Comparative Example 2 is: or =5.690×10 -5 ×e x ······Formula 3-1, where x=4808÷T(R 2 =0.9997);
[0104] According to the curve fitting results of Examples 1 to 3 and Comparative Examples 1 to 2, the theoretical upper limit viscosity curve and the lower limit viscosity curve (i.e., R 2 =1):
[0105] The upper limit viscosity curve fitting equation is: or =1.378×10 -5 ×e x ······Formula 2, where x=5052÷T(R 2 =1);
[0106] The fitting equation of the lower limit viscosity curve is: or =3.461×10 -5 ×e x ······Formula 3, where x=4298÷T(R 2 =1);
[0107] In the above curve fitting equation: or is the viscosity of the electrolyte, in mPa·s; T is the Kelvin temperature, which ranges from 248.15K to 363.15K; e is the base of the natural logarithm, which is approximately equal to 2.71828.
[0108] From the above data and curves, it can be seen that the electrolytes of Examples 1 to 3, whether used with sintered foil or conventional etched foil, have electrolyte viscosities within the range of the upper viscosity curve and the lower viscosity curve in the temperature range of 248.15K to 363.15K, that is, capacitors with better high temperature durability and low temperature stability can be obtained. However, in Comparative Example 1, the viscosity exceeds the upper viscosity curve range in the temperature range of 248.15K to 323.15K; and in Comparative Example 2, the viscosity is lower than the lower viscosity curve range in the temperature range of 283.15K to 363.15K. After the electrolytes of Comparative Examples 1 and 2 are combined with sintered foil, poor low temperature stability or high temperature durability is produced. After the electrolyte in Comparative Example 1 is combined with the sintered foil, its high-temperature durability is not affected, but its low-temperature stability is greatly affected. The reason is that in the temperature range of 248.15K~323.15K (1 / T=0.0031-0.0040), the viscosity exceeds the upper limit viscosity curve range. After the electrolyte in Comparative Example 2 is combined with the sintered foil, although the low-temperature stability is acceptable, after the high-temperature durability test, the capacity has been greatly attenuated (-11.42%), and the loss exceeds three times the initial value. The reason is that in the temperature range of 283.15K~363.15K (1 / T=0.00275-0.0035), the viscosity is lower than the lower limit viscosity curve range. Under high temperature conditions, the viscosity of the electrolyte is lower than the lower limit requirement, and the electrolyte consumption rate will increase, resulting in insufficient high-temperature durability of the capacitor.
[0109] Therefore, by combining an electrolyte that satisfies a specific viscosity-temperature relationship (i.e., within the range of the upper viscosity curve and the lower viscosity curve defined in the present invention) with a sintered foil or a conventional etched foil, an electrolytic capacitor having both high temperature durability and low temperature stability can be obtained.
[0110] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An electrolytic capacitor having both high temperature durability and low temperature stability, characterized in that: The core comprises a positive electrode foil, a negative electrode foil and a separator arranged therebetween; and an electrolyte solution impregnated and permeated into the core; The electrolyte satisfies the exponential relationship curve of the following formula 1: η =A×e x ······Formula 1; Where A is a constant whose value is 1.378×10 -5 ~3.461×10 -5 Within the range; x=B÷T, B is a constant whose value is within the range of 4298~5052; in η is the viscosity of the electrolyte, in mPa·s; T is the Kelvin temperature, which ranges from 248.15K to 363.15K; e is the base of the natural logarithm.
2. The electrolytic capacitor having both high temperature durability and low temperature stability according to claim 1, characterized in that: The exponential relationship curve satisfied by the electrolyte is within the range of the upper limit exponential relationship curve of Formula 2 and the lower limit exponential relationship curve of Formula 3: The upper exponential relationship curve is η =1.378×10 -5 ×e x ······Formula 2, where x=5052÷T; The lower limit exponential relationship curve is η =3.461×10 -5 ×e x ······Formula 3, where x=4298÷T.
3. The electrolytic capacitor having both high temperature durability and low temperature stability according to claim 1, characterized in that: In formula 1, A is a constant whose value is 2.25×10 -5 ~3.48×10 -5 B is a constant whose value is in the range of 4380~4680. The curve fitting degree R of formula 1 is 2 >0.
998.
4. The electrolytic capacitor having both high temperature durability and low temperature stability according to claim 3, characterized in that: The exponential relationship curve satisfied by the electrolyte is η =2.2888×10 -5 ×e x ······Formula 1-1, where x=4658.9÷T, R 2 =0.99885; Or the exponential relationship curve satisfied by the electrolyte is η =2.4938×10 -5 ×e x ······Formula 1-2, where x=4674.9÷T, R 2 =0.99838; Or the exponential relationship curve satisfied by the electrolyte is η =3.4699×10 -5 ×e x ······Formula 1-3, where x=4385.8÷T, R 2 =0.99949.
5. The electrolytic capacitor having both high temperature durability and low temperature stability according to any one of claims 1 to 4, characterized in that: The positive electrode foil is an etched foil or a sintered foil.
6. The electrolytic capacitor having both high temperature durability and low temperature stability according to claim 5, characterized in that: The sintered foil is sintered on the surface of the current collector by sintering metal powder to achieve surface expansion, and the median diameter of particles on the surface is less than or equal to 7 μm.
7. The electrolytic capacitor having both high temperature durability and low temperature stability according to any one of claims 1 to 4, characterized in that: The electrolyte includes a solute and a solvent; The solute is a polyacid ammonium salt and / or a polyacid amine salt; The anions in the polyacid ammonium salt and the polyacid amine salt are each selected from a polycarboxylic acid group or a polyboric acid group; The cation in the polyacid ammonium salt is NH4 + ; The cation in the polyacid amine salt is selected from the primary amine salt NH3R + 、Secondary amine salt NH2R2 + 、Tertiary amine salt NH3R + One of the following, wherein R represents an alkyl group having 1 to 15 carbon atoms.
8. A method for manufacturing an electrolytic capacitor having both high temperature durability and low temperature stability, characterized in that: The method comprises the following steps: forming a core by stacking a positive electrode foil, a separator and a negative electrode foil in a stacking order, impregnating the core with an electrolyte, placing the core in a housing and sealing the housing with a seal; wherein the end of the core has a lead-out foil connected to a lead-out end outside the seal; The electrolyte satisfies the exponential relationship curve of the following formula 1: η =A×e x ······Formula 1; Where A is a constant whose value is 1.378×10 -5 ~3.461×10 -5 Within the range; x=B÷T, B is a constant whose value is within the range of 4298~5052; in η is the viscosity of the electrolyte, in mPa·s; T is the Kelvin temperature, which ranges from 248.15K to 363.15K; e is the base of the natural logarithm.
9. The method for manufacturing an electrolytic capacitor having both high temperature durability and low temperature stability according to claim 8, characterized in that: The exponential relationship curve satisfied by the electrolyte is within the range of the upper limit exponential relationship curve of Formula 2 and the lower limit exponential relationship curve of Formula 3: The upper exponential relationship curve is η =1.378×10 -5 ×e x ······Formula 2, where x=5052÷T; The lower limit exponential relationship curve is η =3.461×10 -5 ×e x ······Formula 3, where x=4298÷T.
10. The method for manufacturing an electrolytic capacitor having both high temperature durability and low temperature stability according to claim 8, characterized in that: In formula 1, A is a constant whose value is 2.25×10 -5 ~3.48×10 -5 B is a constant whose value is in the range of 4380~4680. The curve fitting degree R of formula 1 is 2 >0.
998.
11. The method for manufacturing an electrolytic capacitor having both high temperature durability and low temperature stability according to claim 10, characterized in that: The exponential relationship curve satisfied by the electrolyte is η =2.2888×10 -5 ×e x ······Formula 1-1, where x=4658.9÷T, R 2 =0.99885; Or the exponential relationship curve satisfied by the electrolyte is η =2.4938×10 -5 ×e x ······Formula 1-2, where x=4674.9÷T, R 2 =0.99838; Or the exponential relationship curve satisfied by the electrolyte is η =3.4699×10 -5 ×e x ······Formula 1-3, where x=4385.8÷T, R 2 =0.99949.
12. The method for manufacturing an electrolytic capacitor having both high temperature durability and low temperature stability according to any one of claims 8 to 11, characterized in that: The positive electrode foil is an etched foil or a sintered foil.
13. The method for manufacturing an electrolytic capacitor having both high temperature durability and low temperature stability according to claim 12, characterized in that: The sintered foil is sintered on the surface of the current collector by sintering metal powder to achieve surface expansion, and the median diameter of particles on the surface is less than or equal to 7 μm.
Citation Information
Patent Citations
Electrode material for aluminum electrolytic capacitors and method for manufacturing the electrode material
CN102017034B
Electrolytic solution
JP2005340406A
Electrolytic solution for electric double layer capacitor and electric double layer capacitor
KR1020070022662A